Inter-state Application at the EctHR as a Method to Benefit International Disputes - Zurab Aznaurashvili (European Scientific Journal, ESJ, 2023)
According to the European Convention for the Protection of Human Rights and Fundamental Freedoms, every contracting state has the power to initiate inter-state applications against other states. The use of this procedure is rare due to political and diplomatic reasons; states primarily attempt to resolve disputes through diplomatic means. Despite this, the European Court of Human Rights (ECtHR) has extensive experience, and its decisions and judgments in inter-state conflicts have contributed to positive changes for the disputing parties.The ECtHR consistently aligns with the main goals of the Council of Europe—rule of law, democracy, and human rights—and contributes to the improvement of relations between conflicting parties. This experience holds crucial importance for situations in conflict areas, and the court's case law benefits the relations between the conflicting parties.Inter-state procedures can have a positive impact on the overall situation, and the outcomes can be significant for both parties involved in the conflict. In some conflicts, a legal clarification of facts and recommendations is necessary to initiate further actions and spur negotiations regarding these actions.Therefore, it is evident that there is a clear need for methods within the legal framework and legal procedures to commence the process of improving the situation and pursuing the primary goal of the Council of Europe: achieving peace on the European continent..